Optoelectronic Properties of A‐π‐D‐π‐A Thiophene‐Based Materials with a Dithienosilole Core: An Experimental and Theoretical Study. Issue 9 (6th May 2019) - Caselli, Monica; Vanossi, Davide; Buffagni, Mirko; Imperato, Manuel; Pigani, Laura; Mucci, Adele; Parenti, Francesca
Abstract: Two A‐π‐D‐π‐A thiophene‐based small molecules with a central dithienosilole core and dicyanovinyl (DCV) end groups were synthesized. These compounds differ only by the presence of alkyl and alkylsulfanyl chains, respectively, on the thiophene beta positions. Computational data together with the spectroscopic and electrochemical findings (obtained by means of absorption, steady‐state/time‐resolved emission techniques, and cyclic voltammetry) revealed that both molecules possess low electronic and optical band gaps, broad absorption spectra, and good stability both in p and n‐doping states, which make them suitable for optoelectronic applications. In both compounds, the HOMO–LUMO transition involves an intramolecular charge transfer from the electron‐donor dithienosilole unit to the two terminal electron‐acceptor DCV groups. A marked positive emission solvatochromism was observed for both molecules and was interpreted on the basis of the symmetry breaking in the S1 excited state. The two synthesized compounds were also compared to their shorter precursors and to similar oligothiophenes to understand how the nature of the building block influences the characteristics of the final materials. Furthermore, it was possible to better understand the contribution of the sulfur atom in modulating the optical properties of the small molecules studied. Abstract : Generous donors : Two A‐π‐D‐π‐A thiophene based small molecules with a central dithienosilole core and dicyanovinyl end groups were synthesized. Theoretical calculations, together with spectroscopic and electrochemical findings revealed that both molecules possess low band gaps, broad absorption spectra and a good stability both in p‐ and n‐doping states. The observed increase of the electric dipole moment upon photoexcitation in these quadrupole‐like molecules has been interpreted on the basis of the symmetry breaking in the S1 excited state.